DAMPAK OPOSISI DALAM NOVEL PUSARAN AMUK KARYA ZAKY YAMANI (INTERTEKSTUAL JULIA KRISTEVA) - Abdul Garif; Nensilianti Nensilianti; Suarni Syam Saguni (Fakultas Bahasa dan Sastra Indoensia, 2024)
This research aims to reveal the form of opposition in the novel Pusaran Amuk by Zaky Yamani with three processes, namely opposition, transposition and transformation. Of these three processes, only the opposition process is used. The type of research used is descriptive qualitative research because the data used in this research is in the form of quotations of words, texts, phrases, sentences or paragraphs and does not prioritize numbers. Qualitative methods are used to explore and understand the meaning that comes from social problems and cultural elements in general. The results of the research show the impact of opposition from one person or group to another in the novel Pusaran Amuk. The novel Pusaran Amuk is a legitimization and desacralization of the concept of power.